Highly efficient catalytic hydrosilylation of carbon dioxide by an N-heterocyclic carbene copper catalyst - Zhang, Liang; Cheng, Jianhua; Hou, Zhaomin (Chemical communications (Cambridge, England), 2013)
The N-heterocyclic carbene-copper alkoxide complex [(IPr)Cu(OtBu)] acts as a highly efficient catalyst for the hydrosilylation of carbon dioxide with a hydrosilane. The desired product, silyl formate could be isolated in multigram quantity under solvent free conditions. A copper formate catalyst intermediate was successfully isolated and structurally characterized, thus offering important insight into the mechanistic details.